Statistical Analysis Engine Capacity, Weight, and Torque on MPV Fuel Consumption Using Regression and Correlation Algorithms - Salafuddin, Hafidz; Pradipta, Nanang K; Adnan, Farrah Anis Fazliatul; Rhee, Jong Soo; Ginting, Dianta (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
The rapid increase in production and usage of Multi-Purpose Vehicles (MPVs) in Indonesia has led to heightened concerns over fuel consumption, environmental pollution, and economic sustainability. This study investigates the relationship between engine capacity, vehicle weight, engine torque, and fuel consumption in MPVs, aiming to provide a better understanding of how these variables influence fuel efficiency. Data from 1500 cc MPV models produced between 2023 and 2024 were collected, including technical specifications such as engine capacity, weight, torque, and reported fuel consumption. Using MATLAB, linear regression and Pearson correlation analysis were employed to analyze these relationships. The results reveal that vehicle weight has the most significant impact on fuel efficiency, exhibiting a strong negative correlation of -0.69, meaning that heavier vehicles tend to consume more fuel. Engine capacity showed a moderate negative correlation of -0.28, while engine torque had a weak correlation of -0.11, indicating that torque plays a less critical role in determining fuel consumption under normal driving conditions. The regression analysis further confirmed that vehicle weight is the most influential factor, with reductions in weight providing the greatest potential for improving fuel efficiency. These findings have important implications for both manufacturers and consumers. Automotive manufacturers are encouraged to prioritize the use of lightweight materials and advanced engineering designs to enhance fuel efficiency. Additionally, consumers can use this information to make informed decisions when selecting MPVs, focusing on models with optimized weight to reduce fuel consumption. Overall, this study contributes to ongoing efforts to develop more sustainable and fuel-efficient vehicles in the automotive industry.